The Effect of Internship and Work Motivation on Students' Work Readiness in Vocational Education: PLS-SEM Approach - Azhar Fauzan; Mochamad Bruri Triyono; Rendra Ananta Prima Hardiyanta; Rihab Wit Daryono; Shilmi Arifah (Yayasan Keluarga Guru Mandiri, 2023)
Industrial apprenticeship experience has not been realized optimally towards student work readiness. So that the process of factualization and comparing theoretical knowledge with actual situations and conditions in the world of work becomes less than optimal. In addition, students' work motivation to be ready to work is still in the low category. This study aims to reveal the effect of internship experience and work motivation on work readiness. The sampling technique used simple random sampling and obtained research respondents as many as 450 students in 5 vocational education schools in Yogyakarta. The combination of factor analysis and regression analysis was used to analyze the data using second-order PLS-SEM analysis. Convergent and discriminant validity, and internal consistency reliability has met the test requirements. Evaluation of the structural model shows the value of effect size (f2) with a large effect, the determination coefficient (R2) of the variable is 65.90%, and the predictive relevance (Q2) is 51.10%. Hypothesis testing is based on the Î²-coefficient, Ï-value, dan T-statistic values that have met the cut-off values suggested in the literature. So that all hypotheses Ha is accepted which indicates that there is a positive and significant effect on the internship experience and motivation on student work readiness. Schools are expected to provide encouragement for work motivation and review the apprenticeship process from planning to implementation in the field so as to increase student work readiness.